The Global Financial and Economic Crisis: Did HRD Play a Role?. (February 2014) - MacKenzie, Clíodhna; Garavan, Thomas N.; Carbery, Ronan
The Problem: The Global Financial and Economic Crisis 1 starting in 2007 and its resultant impact has called into question the contribution of Human Resource Development (HRD) strategies and practices to the crisis. With its primary focus on the development of human resources, it could be argued that HRD aligned itself too closely with the strategic goals of organizations, often times profit centric, and failed to provide leaders with the skills, knowledge, and values required to question the decisions made by organizations in the pursuit of profit goals and the development of a culture of risk taking. The Solution: Utilizing Cognitive Appraisal Theory (CAT), this article draws on the official reports and public inquiry hearings in the United States, United Kingdom, and Ireland into the financial crisis and finds that HRD strategies, practices, and processes are factors which may have contributed to a culture of excessive risk taking and ineffective decision making. We outline the implications for HRD theory and practice. The Stakeholders: The research findings inform a multiplicity of stakeholders including organizational behaviorists, social psychologists, government bodies, educational organizations, and scholars researching strategic HRD in organizations.